Prospects and Challenges of Using Social Sites in Higher Education - Muhammad Sarwar, Muhammad Perveiz,Mubashar Nadeem (PJE, 2023)
he difference between the skills desired to carry out assessments tasks and t he s kills a ctually a cquired du ring p re-service t eaching t raining program by prospective teachers is being referred to as skills’ gap. The study dr aws i ts ba sis from 5 th national professional s tandards f or teachers, which describes necessary assessment skills for teachers